A lithium-sulfur solid-state battery
Patent Information
- Application Number
- CN202510520164.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-24
- Publication Date
- 2026-10-27
AI Technical Summary
[0045]1. 采用三维限域硫正极,通过聚多巴胺包覆3DG负载硫,并调控3DG材料层级孔隙,实现了硫的物理-化学双限域,有效抑制了硫正极在循环过程中的体积膨胀,从而提高了电池的循环稳定性和使用寿命;
Smart Images

Figure CN122992003A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of batteries, and more specifically to a lithium-sulfur solid-state battery. Background Technology
[0002] Lithium-sulfur batteries, as a new generation of high-energy-density energy storage systems, have a theoretical specific energy of up to 2600 Wh / kg and excellent application prospects. However, existing liquid electrolyte lithium-sulfur batteries suffer from problems such as polysulfide shuttle effect, high self-discharge, and poor safety performance, which seriously limit their practical application. Using solid electrolytes can suppress the shuttle effect, but lithium dendrites are easily generated on the lithium metal anode during charge and discharge, leading to a decline in battery cycle performance and safety performance, becoming a key bottleneck restricting the development of solid-state lithium-sulfur batteries.
[0003] Patent CN117154182A discloses a solid-state silicon-sulfur battery with a gradient electrolyte composition. The battery includes a silicon anode, a sulfur cathode, and a bilayer gradient solid-state electrolyte. The silicon anode is made from silicon powder, lithium powder, a conductive agent, and a binder; the sulfur cathode is made from sublimed sulfur, carbon nanotubes, a conductive agent, and a binder; the bilayer gradient solid-state electrolyte comprises a porous lithium titanium aluminum phosphate electrolyte framework and a polyvinylidene fluoride-hexafluoropropylene layer. Although this patent uses a bilayer gradient solid-state electrolyte to match the electrodes, there are still issues regarding the need to further improve the ionic conductivity and interfacial compatibility of the bilayer gradient solid-state electrolyte with the electrodes. Summary of the Invention
[0004] In existing technologies, lithium-sulfur batteries suffer from problems such as polysulfide shuttle effect, high self-discharge rate, and poor safety performance. While using a solid electrolyte can suppress the polysulfide shuttle effect to some extent, lithium dendrites easily form on the metallic lithium anode during charge and discharge, leading to a decline in battery cycle performance and safety. Simultaneously, there is currently a lack of effective methods to achieve the confinement effect of the sulfur cathode and suppress its volume expansion during charge and discharge. To address these technical problems, this invention provides a lithium-sulfur solid-state battery, comprising a three-dimensionally confined sulfur cathode, a solid electrolyte, and a lithium composite anode, which can effectively suppress polysulfide shuttle, reduce the generation and growth of lithium dendrites, reduce side reactions, and suppress the volume expansion of both the cathode and anode.
[0005] The inventors discovered that this invention, through a unique structural design, effectively solves two core challenges in lithium-sulfur batteries: the shuttle effect of sulfur in the positive electrode and the dendrite growth of lithium in the negative electrode. On the positive electrode side, a composite structure of polydopamine (PDA)-coated three-dimensional graphene (3DG) loaded with sulfur is employed. By precisely controlling the multi-level pore system of the three-dimensional graphene, a dual synergistic effect of physical confinement and chemical adsorption of sulfur is achieved: the macroporous structure of the three-dimensional graphene provides a high loading space for sulfur, while the mesopores and micropores effectively restrict the diffusion of polysulfides. The PDA coating layer, through its abundant polar functional groups, strongly chemically adsorbs polysulfides, significantly suppressing the "shuttle effect." On the negative electrode side, the innovative boron nitride nanotube spatial layer design has three advantages: first, the high mechanical strength of the BNNT film effectively resists lithium dendrite penetration; second, its nano-network structure provides a uniform storage space for lithium ions, guiding uniform lithium deposition; and third, the chemical stability of BNNT avoids side reactions with lithium metal.
[0006] Specifically, the present invention provides a lithium-sulfur solid-state battery, the lithium-sulfur solid-state battery comprising, in sequence:
[0007] A three-dimensional confined sulfur cathode, wherein the three-dimensional confined sulfur cathode comprises polydopamine (PDA) coated three-dimensional graphene (3DG) loaded with sulfur;
[0008] Solid electrolytes; and
[0009] A lithium composite anode, comprising a lithium / lithium alloy anode and a space layer on the anode surface, wherein the space layer on the anode surface is a boron nitride nanotube (BNNT) composite film.
[0010] The positive electrode proposed in this invention uses a PDA layer to coat 3DG / S. This is because the polar functional groups on the surface of PDA can form stable chemical bonds with polysulfides, effectively inhibiting the dissolution and shuttle of polysulfides. The PDA coating layer acts as a buffer interface, alleviating the damage to the electrode structure caused by sulfur volume expansion and maintaining the integrity of the three-dimensional conductive network. The physical-chemical dual confinement effect of PDA and 3DG fixes sulfur in multi-level channels, improving the utilization rate of active sulfur.
[0011] Optionally, the three-dimensional confined sulfur cathode achieves dual confinement of sulfur through physical adsorption and chemical bonding by regulating the hierarchical pore structure of 3DG.
[0012] Optionally, the thickness of the PDA layer coating is 5-50 nm, and the coating rate is ≥90%.
[0013] Optionally, the 3DG is three-dimensional honeycomb graphene.
[0014] Optionally, the 3DG has a hierarchical porosity, including macropores with a diameter of 50-500 nm, mesopores with a diameter of 2-50 nm, and micropores with a diameter of <2 nm, and a specific surface area of 500-5000 m². 2 / g.
[0015] Optionally, the active sulfur includes elemental sulfur, sulfurized polyacrylonitrile, or a combination thereof.
[0016] Optionally, the sulfur loading of the 3DG is 60-90%.
[0017] Optionally, the space layer BNNT composite film in the lithium composite anode is formed by coating a transfer film with a mixture of BNNT and lithium salt.
[0018] Optionally, the BNNT has a diameter of 10-500 nm, a length of 1-100 μm, and an elastic modulus ≥0.5 TPa.
[0019] Optionally, the BNNT includes one or a combination of at least two of single-walled boron nitride nanotubes, multi-walled boron nitride nanotubes, and nanoribbon boron nitride.
[0020] Optionally, the adhesion between the transfer film and the lithium composite anode is 1-8 g / inch, and the thickness is 20-100 μm.
[0021] Optionally, the thickness of the space layer is 1-100 μm and the Young's modulus is ≥6 GPa.
[0022] Optionally, the BNNT mixture slurry comprises BNNT, lithium salt, binder, and hydrophilic additive.
[0023] Optionally, the mass ratio of BNNT, lithium salt, binder and hydrophilic additive is (1-20):(1-5):(1-5):(0.5-2).
[0024] Optionally, the lithium salt includes one or more combinations of lithium fluoride, lithium nitride, lithium hexafluorophosphate, lithium trifluoromethanesulfonate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium perchlorate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium dioxalateborate, lithium difluorooxalateborate, lithium carbonate, lithium oxalate, lithium bicarbonate, lithium acetate, lithium halide, lithium sulfate, and lithium hydroxide.
[0025] Optionally, the adhesive comprises one or a combination of at least two of the following: polyvinyl alcohol, polyethylene oxide, polybutene-styrene, polystyrene-butadiene copolymer, polyvinylidene fluoride, polystyrene, polycarboxylic cellulose, cyanoacrylate, cyclodextrin, cyclic ether derivatives, polyurethane, methacrylate, epoxy resin, vinyl acetate polymer, polyimide, organofluoropolymer, organosiloxane, polyethylene glycol, polyethylene, polyvinyl chloride, polypropylene, glycerol, ethylparaben, and their derivatives.
[0026] Optionally, the hydrophilic additive includes one or more combinations of carboxylates, sulfonates, sulfates, phosphates, imidazole ionic liquids, pyridine ionic liquids, quaternary ammonium ionic liquids, quaternary phosphonium ionic liquids, pyrrolidine ionic liquids, and piperidine ionic liquids.
[0027] Optionally, the transfer film material includes an organic material selected from one or more of polyvinylidene fluoride, polyvinyl chloride, polyethylene, polypropylene, polystyrene, styrene-butadiene-vinyl nitrile copolymer, polyimide, polycarbonate, phenolic plastics, polyoxymethylene, polyethylene terephthalate, styrene-modified polymethacrylic acid, polysulfone, polytetrafluoroethylene, amino plastics, and epoxy resin, or their homopolymers or copolymers.
[0028] Optionally, the lithium / lithium alloy anode includes one or a combination of metallic lithium anode, lithium alloy anode, and lithium alloy anode.
[0029] Preferably, the lithium alloy anode comprises an alloy of lithium with one or more of silicon, indium, silver, carbon, magnesium, aluminum, boron, tin, gallium, cobalt, gold, barium, bismuth, calcium, germanium, mercury, platinum, zinc, lead, antimony, cadmium, and cobalt.
[0030] The thickness of the lithium / lithium alloy anode is 3μm-300μm, preferably 10μm-100μm.
[0031] Optionally, the thickness ratio of the space layer to the lithium / lithium alloy anode is (0.001-1):1, preferably (0.01-0.1):1.
[0032] Optionally, the solid electrolyte comprises one or more of the following: sulfide solid electrolyte, oxide solid electrolyte, halide solid electrolyte, polymer solid electrolyte, or organic-inorganic composite solid electrolyte.
[0033] Optionally, both the functionalized positive electrode and the lithium composite negative electrode include a current collector, which includes at least one of copper foil, aluminum foil, stainless steel foil, nickel foil, tin foil, carbon nanotube paper, carbon fiber paper, copper mesh, aluminum mesh, stainless steel mesh, nickel foam, and organic fiber film with metal plating on the surface.
[0034] Another aspect of the present invention provides a method for preparing a lithium-sulfur solid-state battery as described above, the method comprising:
[0035] (1) Preparation of PDA-coated 3DG-loaded sulfur mixture: 3DG is immersed in a buffer solution containing PDG and stirred for 6-12 hours to obtain PDA-coated 3DG composite material; sulfur powder and PDA-coated 3DG are uniformly mixed and heated to the melting point of sulfur (115℃) to melt the sulfur and penetrate into the graphene pores to obtain PDA-coated 3DG / S mixture;
[0036] (2) Preparation of functionalized positive electrode: The above PDA-coated 3DG / S mixture is uniformly mixed with a binder, and a solvent is optionally added; the prepared mixed slurry is loaded onto the surface of the current collector and dried to obtain a functionalized positive electrode film;
[0037] (3) Preparation of lithium composite negative electrode space layer: BNNT, lithium salt, binder and hydrophilic additive are uniformly mixed, and an optional solvent is added and stirred to obtain a mixed slurry. The mixed slurry is placed on the transfer film and dried to obtain the lithium composite negative electrode space layer.
[0038] (4) Preparation of lithium composite anode: The space layer film is rolled onto the surface of the lithium / lithium alloy anode and the tabs are welded to obtain the lithium composite anode;
[0039] (5) Assemble lithium-sulfur solid-state batteries: Assemble functionalized positive electrode, solid electrolyte, lithium composite negative electrode and encapsulation materials into lithium-sulfur solid-state batteries.
[0040] Optionally, the uniform mixing method in step (1) is ball milling, wherein the ball milling speed is 100-600 rpm and the ball milling time is 3-6 h; the drying in steps (2) and (3) is 80-100℃ and the drying time is 8-12 h; the binder in step (2) includes polyvinylidene fluoride (PVDF), polyacrylic acid (PAA), sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber. (SBR), sodium alginate (SA), polyethylene oxide (PEO) or polyimide (PI); the solvents in steps (2) and (3) include any one or a combination of at least two of N-methylpyrrolidone, tetrahydrofuran, dimethyl ethyl ether, dichloromethane, ethylene carbonate, dimethyl carbonate, diethyl carbonate, diethyl carbonate, methyl ethyl carbonate, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, diethylene glycol monomethyl ether, tetraethylene glycol dimethyl ether, dimethyl sulfate, and polyetherketone.
[0041] Optionally, in step (2), the PDA coating 3DG / S: binder: solvent = (5-10): (2-3): (87-93).
[0042] Optionally, the method of applying the paste to the transfer film in step (3) includes any one or a combination of at least two of coating, spraying, spin coating, rolling, and impregnation;
[0043] In step (4), the pressure at which the space layer obtained in step (3) is rolled onto the lithium / lithium alloy negative electrode is 10-20 kN.
[0044] This invention has at least one of the following beneficial technical effects:
[0045] 1. A three-dimensional confined sulfur cathode is adopted. By coating 3DG with polydopamine and loading sulfur, and controlling the layered porosity of 3DG material, the physical-chemical dual confinement of sulfur is achieved, which effectively suppresses the volume expansion of sulfur cathode during cycling, thereby improving the cycle stability and service life of the battery.
[0046] 2. A lithium composite anode is adopted, wherein the spatial layer on the surface of the anode is a boron nitride nanotube film, which increases the mechanical strength of the lithium anode interface, provides storage space for lithium ions, effectively reduces the generation and growth of lithium dendrites, and improves the safety performance of the battery.
[0047] 3. This lithium-sulfur solid-state battery solves the problems of existing lithium-sulfur batteries by designing a three-dimensional confined sulfur cathode and lithium composite anode, improving the battery's energy density, cycle performance, and safety performance, and laying the foundation for the commercial application of lithium-sulfur batteries. Attached Figure Description
[0048] Figure 1 This is a schematic diagram of the lithium-sulfur solid-state battery structure of the present invention;
[0049] Figure 2 This is a schematic diagram of lithium-ion deposition when the lithium composite anode of the present invention is applied to a lithium-sulfur solid-state battery;
[0050] Figure 3 The image shows a 1000x magnified SEM image of the lithium composite anode space layer after 300 cycles of the lithium-sulfur solid-state battery in Example 1.
[0051] Figure 4 An atomic force microscope image of the lithium composite negative electrode space layer in the lithium-sulfur solid-state battery of Example 1;
[0052] Figure 5 The cycling test curves of the lithium-sulfur solid-state batteries in Examples 1, 2, 3 and Comparative Example 1 at a charge-discharge current of 0.5C are shown.
[0053] Among them, 1-positive current collector, 2-functionalized sulfur positive electrode, 2-1-three-dimensional graphene-supported sulfur, 2-2-PDA coating layer, 3-solid electrolyte, 4-spatial layer, 5-lithium / lithium alloy negative electrode, 6-negative current collector. Detailed Implementation
[0054] To facilitate understanding of the present invention, the following embodiments are provided. Those skilled in the art should understand that these embodiments are merely illustrative and should not be construed as limiting the scope of the invention.
[0055] An example illustrating the structure of the lithium-sulfur solid-state battery provided by this invention is shown in the schematic diagram below. Figure 1 As shown. The functionalized positive electrode includes a positive electrode current collector 1 and a functionalized sulfur positive electrode 2; the lithium composite negative electrode includes a space layer 4, a lithium / lithium alloy negative electrode 5, and a negative electrode current collector 6. A solid electrolyte 3 is located between the functionalized positive electrode and the lithium composite negative electrode, and the solid electrolyte 3 is in contact with the space layer 4.
[0056] Example 1
[0057] This embodiment provides a lithium-sulfur battery, comprising a functionalized positive electrode consisting of a 1000nm pore size three-dimensional graphene-loaded 80% elemental sulfur coated with a PDA, a 20nm PDA coating thickness, a sulfide solid electrolyte, a 10μm thick BNNT space layer, and a 50μm thick lithium metal negative electrode. The space layer is composed of 200nm diameter, 50μm length BNNT, lithium fluoride (LiF), polyethylene oxide (PEO), N-ethylpyridine bromide, and the solvent N-methylpyrrolidone (NMP), with a BNNT:LiF:PEO:N-ethylpyridine bromide:NMP ratio of 10:3:2:1:84. The Young's modulus of the space layer is 10 GPa. The positive electrode current collector is aluminum foil, and the negative electrode current collector is copper foil.
[0058] The method for preparing the lithium-sulfur battery includes the following steps:
[0059] (1) Preparation of three-dimensional graphene-loaded sulfur mixture: 3DG was immersed in a buffer solution containing PDG and stirred for 6 hours to obtain PDA-coated 3DG composite material; sulfur powder and PDA-coated 3DG were mixed evenly and heated to the melting point of sulfur 115℃ to melt the sulfur and penetrate into the graphene pores to obtain PDA-coated 3DG / S mixture.
[0060] (2) Preparation of functionalized positive electrode: The above PDA-coated 3DG / S mixture is uniformly mixed with SBR and NMP; the prepared mixed slurry is loaded onto the surface of the current collector and dried at 80°C to obtain a functionalized positive electrode film;
[0061] (3) Preparation of lithium composite negative electrode space layer: BNNT, LiF, PEO, N-ethylpyridine bromide and NMP are uniformly mixed to obtain a mixed slurry. The mixed slurry is coated on a 30 μm PET film and dried at 80℃ to obtain a lithium composite negative electrode space layer.
[0062] (4) Preparation of lithium composite anode: Press the space layer film material with a 10kN force roller onto the surface of the lithium / lithium alloy anode, and weld the electrode tabs to obtain the lithium composite anode;
[0063] (5) Assemble lithium-sulfur solid-state batteries: Assemble functionalized positive electrode, solid electrolyte, lithium composite negative electrode and encapsulation materials into lithium-sulfur solid-state batteries.
[0064] Example 2
[0065] This embodiment provides a lithium-sulfur battery, comprising a functionalized positive electrode consisting of 1500 nm pore size three-dimensional graphene loaded with 80% elemental sulfur, a sulfide solid electrolyte, a PDA coating thickness of 20 nm, a BNNT space layer thickness of 10 μm, and a lithium metal negative electrode thickness of 50 μm. The space layer is composed of BNNT with a diameter of 300 nm and a length of 50 μm, lithium bis(fluorosulfonyl)imide (LiFSI), SBR, sodium dodecylbenzenesulfonate (SDBS), and the solvent dimethyl ethylene glycol (DME), with a BNNT:LiFSI:SBR:SDBS:DME ratio of 10:3:2:1:84 and a Young's modulus of 8 GPa. The positive electrode current collector is aluminum foil, and the negative electrode current collector is copper foil.
[0066] The preparation method of the lithium-sulfur battery is the same as that in the example.
[0067] Example 3
[0068] This embodiment provides a lithium-sulfur battery, comprising a functionalized positive electrode with a pore size of 1000 nm, supported on 80% sulfurized polyacrylonitrile (PNA), a sulfide solid electrolyte, a PDA coating thickness of 20 nm, a BNNT space layer thickness of 10 μm, and a lithium metal negative electrode thickness of 50 μm. The space layer is composed of BNNTs with a diameter of 300 nm and a length of 30 μm, lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), polyvinylidene fluoride (PVDF), 1-methylimidazolium chloride, and dimethyl carbonate as the solvent, with a ratio of BNNT:LiTFSI:PVDF:1-methylimidazolium chloride:dimethyl carbonate = 10:3:1:1:85. The Young's modulus of the space layer is 6 GPa. The positive electrode current collector is aluminum foil, and the negative electrode current collector is copper foil.
[0069] The preparation method of the lithium-sulfur battery is the same as that in the example.
[0070] Example 4
[0071] Compared with Example 1, the only difference is that the amount of elemental sulfur supported on the three-dimensional graphene is replaced with 60%, while the other conditions remain the same.
[0072] Example 5
[0073] Compared with Example 1, the only difference is that the amount of elemental sulfur loaded on the three-dimensional graphene is replaced with 90%, while the other conditions remain the same.
[0074] Example 6
[0075] Compared with Example 1, the only difference is that the thickness of the PDA coating layer is replaced with 5nm, while the other conditions remain the same.
[0076] Example 7
[0077] Compared with Example 1, the only difference is that the thickness of the PDA coating layer is replaced with 50nm, while the other conditions remain the same.
[0078] Example 8
[0079] Compared with Example 1, the only difference is that the solid electrolyte is replaced with an oxide solid electrolyte, while the other conditions remain the same.
[0080] Example 9
[0081] Compared with Example 1, the only difference is that the thickness of the BNNT space layer is replaced with 1 μm, while the other conditions remain the same.
[0082] Example 10
[0083] Compared with Example 1, the only difference is that the thickness of the BNNT space layer is replaced with 100 μm, while the other conditions remain the same.
[0084] Example 11
[0085] Compared with Example 1, the only difference is that the proportion of BNNT in the slurry is replaced with 20%, while the other conditions remain the same.
[0086] Example 12
[0087] Compared with Example 1, the only difference is that the proportion of BNNT in the slurry is replaced with 1%, while the other conditions remain the same.
[0088] Example 13
[0089] Compared with Example 1, the only difference is that the LiF content in the slurry is replaced with 5% by mass, while the other conditions remain the same.
[0090] Example 14
[0091] Compared with Example 1, the only difference is that the LiF content in the slurry mass ratio is replaced with 1%, while the other conditions remain unchanged.
[0092] Example 15
[0093] Compared with Example 1, the only difference is that the proportion of PEO in the slurry is replaced with 5%, while the other conditions remain the same.
[0094] Example 16
[0095] Compared with Example 1, the only difference is that the proportion of PEO in the slurry is replaced with 1%, while the other conditions remain the same.
[0096] Example 17
[0097] Compared with Example 1, the only difference is that the hydrophilic additive is replaced with 2% of the slurry mass, while the other conditions remain the same.
[0098] Example 18
[0099] Compared with Example 1, the only difference is that the hydrophilic additive is replaced with 0.5% of the slurry mass, while the other conditions remain the same.
[0100] Example 19
[0101] Compared with Example 1, the only difference is that the lithium metal anode is replaced with a 5μm electrode, while the other conditions remain the same.
[0102] Example 20
[0103] Compared with Example 1, the only difference is that the lithium metal anode is replaced with a 100μm electrode, while the other conditions remain the same.
[0104] Example 21
[0105] Compared with Example 1, the only difference is that the lithium metal anode is replaced with a lithium aluminum alloy anode, while the other conditions remain the same.
[0106] Example 22
[0107] Compared with Example 1, the only difference is that the space layer is applied to the transfer film using a spraying method, while all other conditions remain the same.
[0108] Comparative Example 1
[0109] This comparative example provides a lithium-sulfur solid-state battery. Compared with Example 1, elemental sulfur is directly coated on aluminum foil as the positive electrode without adding a space layer, and a 50μm lithium metal strip is used as the negative electrode, while other conditions remain unchanged.
[0110] Comparative Example 2
[0111] This comparative example provides a lithium-sulfur solid-state battery. Compared with Comparative Example 1, the sulfide solid electrolyte is replaced with an oxide solid electrolyte, while the other conditions remain unchanged.
[0112] Comparative Example 3
[0113] This comparative example provides a lithium-sulfur solid-state battery that, compared to Example 1, does not use PDA coating, while all other conditions remain the same.
[0114] Comparative Example 4
[0115] This comparative example provides a lithium-sulfur solid-state battery. Compared with Example 1, elemental sulfur is directly coated on aluminum foil as the positive electrode, while other conditions remain unchanged.
[0116] Comparative Example 5
[0117] This comparative example provides a lithium-sulfur solid-state battery that, compared to Example 1, does not add a space layer, uses a 50μm lithium metal strip as the negative electrode, and keeps all other conditions unchanged.
[0118] Comparative Example 6
[0119] This comparative example provides a lithium-sulfur solid-state battery. Compared with Example 1, a two-dimensional graphene sheet loaded with elemental sulfur coated on an aluminum foil is used as the positive electrode, while the other conditions remain unchanged.
[0120] Comparative Example 7
[0121] This comparative example provides an all-solid-state battery that, compared to Example 1, does not contain BNNT material in its space layer, while the other conditions are the same as in Example 1.
[0122] Comparative Example 8
[0123] This comparative example provides an all-solid-state battery that, compared to Example 1, does not contain lithium salt in its space layer, while the other conditions are the same as in Example 1.
[0124] Comparative Example 9
[0125] This comparative example provides an all-solid-state battery that, compared to Example 1, does not contain a binder in its space layer, while the other conditions are the same as in Example 1.
[0126] Comparative Example 10
[0127] This comparative example provides an all-solid-state battery that, compared to Example 1, does not contain hydrophilic additives in its space layer, while the other conditions are the same as in Example 1.
[0128] Comparative Example 11
[0129] This comparative example provides an all-solid-state battery. Compared with Example 1, its spatial layer is replaced with a transfer Al2O3 coating, and the other conditions are the same as those in Example 1.
[0130] Comparative Example 12
[0131] This comparative example provides an all-solid-state battery, which, compared to Example 1, has its spacer layer replaced with a LiF coating, while the other conditions are the same as in Example 1.
[0132] The preparation method of lithium-sulfur solid-state battery is as follows: Take 100mg of solid electrolyte and press it into a Teflon pressing mold at a pressure of 300MPa to obtain an electrolyte layer; press the obtained functionalized positive electrode sheet onto one side of the solid electrolyte at a pressure of 300MPa, and then press the lithium composite negative electrode onto the other side of the electrolyte layer at a pressure of 20MPa to obtain an all-solid-state battery.
[0133] Lithium-sulfur solid-state battery performance testing:
[0134] Solid-state batteries were assembled using the positive and negative electrodes provided in Examples 1-22 and Comparative Examples 1-12, respectively, and their cycle performance was tested. The specific test method was as follows: constant current charging and constant current discharging were performed at 25°C, with a charging and discharging voltage range of 1.7-2.8V and a charging and discharging rate of 0.5C. The initial capacity of the battery was recorded as C0. One full charge and discharge cycle was recorded as one cycle. The charging and discharging were performed according to the above method, and the capacity of the battery was tested after each cycle until the battery capacity was 80% of C0, or the battery experienced a short circuit or the charging and discharging efficiency was lower than 98%. The number of cycles at this point was recorded.
[0135] Young's modulus test of lithium composite anode:
[0136] A space layer was placed on a lithium metal anode, and Young's modulus was measured at the anode interface. Using an atomic force microscope, one end of a microcantilever, highly sensitive to minute forces, was fixed, while the other end had a tiny needle tip that gently contacted the interface. During scanning, the repulsive force between the tip and the interface was kept constant. The microcantilever with the tip moved undulating perpendicular to the interface, corresponding to the equipotential surface of the interatomic forces between the tip and the interface. Using optical detection or tunneling current detection, the positional changes of the microcantilever at various scanning points could be measured, thus obtaining the sample morphology and calculating the Young's modulus.
[0137] Adhesion test of transfer film to lithium composite anode:
[0138] Using a tensile testing machine, the transfer film and lithium composite negative electrode were peeled off at a uniform speed at an angle of 180°, and the maximum force value during the peeling process was recorded to evaluate the adhesion strength.
[0139] The cycle performance test results of the lithium-sulfur all-solid-state batteries prepared using Examples 1-22 and Comparative Examples 1-12 are shown in Table 1.
[0140] Table 1 Battery Cycle Performance Test Results
[0141]
[0142] Battery cycle performance test analysis results:
[0143] (1) Comparison of Examples 1-3 and Comparative Example 1
[0144] Examples 1-3 provide a high-performance lithium-sulfur solid-state battery, wherein the positive electrode adopts a 3DG sulfur-locking structure coated with polydopamine (PDA), and the negative electrode adopts a lithium metal strip with a BNNT layer modification layer. In contrast, the comparative examples use elemental sulfur as the positive electrode and ordinary lithium strip as the negative electrode. According to Table 1 and... Figure 4 Test results show that the batteries of Examples 1-3 are significantly superior to Comparative Example 1 in terms of cycle stability, energy density, and safety. Specifically, the capacity retention of the batteries of Examples 1-3 decreased to 80% after 200 cycles at 0.5C, while that of the comparative example decreased to 80% after 60 cycles at 0.5C. This is attributed to the effective suppression of the polysulfide shuttle effect by the conductive network of 3DG and the polar adsorption of PDA, while the BNNT layer homogenizes the lithium-ion flow, reduces lithium dendrite growth, and increases the interfacial Young's modulus to 10 GPa (e.g., ...). Figure 3 , Figure 4 Therefore, this embodiment significantly improves the overall performance of lithium-sulfur solid-state batteries through synergistic optimization of the positive and negative electrodes.
[0145] (2) Comparison of Example 1 and Examples 4-7
[0146] Examples 4-7 illustrate the effects of varying sulfur loading on three-dimensional graphene and different PDA coating thicknesses on the cycle performance of lithium-sulfur solid-state batteries. According to the test data in Table 1, when the sulfur loading is 60%, the utilization rate of the sulfur active material is high, effectively mitigating volume expansion, but the overall energy density of the battery is low. When the sulfur loading is 90%, the specific capacity of the battery increases, but the number of cycles decreases, which is attributed to the increased volume expansion under high sulfur content. Furthermore, optimizing the PDA coating thickness has a significant impact on performance: a 5nm PDA coating that is too thin lacks mechanical strength and chemical stability, reduces the physical / chemical adsorption capacity for polysulfides, and cannot effectively suppress the shuttle effect; while a 50nm PDA coating that is too thick hinders ion transport, resulting in decreased cycle performance.
[0147] (3) Comparison of Example 8 and Comparative Example 2
[0148] Example 8 and Comparative Example 2 illustrate the effect of the lithium-sulfur solid-state battery proposed in this invention on cycle performance in different types of solid electrolytes. The data in Table 1 show that in oxide electrolytes, the lithium-sulfur solid-state battery cycled 108 times more. The combination of PDA-coated three-dimensional graphene for sulfur locking and the lithium composite anode in sulfide solid electrolytes can suppress polysulfide shuttle, improve interfacial contact in oxide electrolytes or other solid electrolytes, and the flexible interface of BNNT can adapt to electrolyte deformation and reduce interfacial impedance.
[0149] (4) Comparison of Example 1 and Examples 9-20
[0150] Examples 9-20 illustrate the thickness and composition of the lithium composite anode space layer, and the impact of changes in the active material layer thickness on the cycle performance of lithium-sulfur solid-state batteries. Data in Table 1 shows that the thickness of the BNNT space layer directly affects lithium-ion transport and dendrite suppression: too thin a layer results in insufficient mechanical strength, making it difficult to effectively block dendrites; too thick a layer increases interfacial impedance and reduces rate performance. The ratio of BNNT / binder / lithium salt / hydrophilic additive needs to be optimized synergistically. High BNNT content enhances ion storage and mechanical support, but excessive amounts increase interfacial impedance; too much binder clogs pores, while too little reduces the mechanical properties of the space layer; lithium salt improves ionic conductivity, but excessive amounts can easily trigger side reactions, while too little reduces ion conduction performance; hydrophilic additives reduce the surface tension of the solution on the transfer film, but their content needs to be controlled to avoid interfacial instability. The thickness of the lithium metal layer affects the battery's energy density and cycle performance; too thin a layer easily leads to local depletion and short circuits, while too thick a layer exacerbates volume expansion.
[0151] (5) Comparison of Example 1 and Example 21
[0152] Example 21 illustrates the effect of different lithium alloy anodes on the cycle performance of lithium-sulfur solid-state batteries. Lithium alloy anodes exhibit higher mechanical strength and dimensional stability, effectively suppressing volume expansion and electrode pulverization during lithium deposition / stripping, and reducing irreversible loss of active lithium. The inherent lithiophilicity of lithium alloys reduces lithium nucleation overpotential, promotes uniform lithium deposition, and alleviates the shuttle effect of polysulfides in the sulfur cathode. Furthermore, the alloy phase acts as a stable lithium-conducting framework, reducing electrolyte side reactions and lowering the rate of interfacial impedance growth. Data in Table 1 shows that the cycle performance of the lithium alloy composite battery is improved, with an increase of 60 cycles at a 0.5C charge / discharge rate.
[0153] (6) Comparison of Example 1 and Example 22
[0154] Example 22 illustrates the impact of different transfer processes for the space reinforcement layer on the performance of lithium-sulfur solid-state batteries. The coating method is replaced with a spraying method. The spraying method requires ensuring the uniformity of the space reinforcement layer slurry sprayed onto the transfer surface and controlling the surface tension of the lithium metal strip during drying. By controlling the process parameters, different coating processes can be substituted.
[0155] (7) Comparison of Example 1 and Comparative Examples 3-5
[0156] The comparative examples illustrate the effects of PDA coating, three-dimensional graphene sulfur locking, and BNNT spatial layers on the cycle performance of lithium-sulfur solid-state batteries. In Comparative Example 3, the lack of a PDA coating exacerbates polysulfide dissolution and shuttle phenomena due to its polar adsorption and chemical anchoring effects, leading to significant capacity decay. In Comparative Example 4, the lack of three-dimensional graphene sulfur locking reduces the conductive network and physical sulfur-limiting ability of the cathode, resulting in uneven sulfur species distribution, reduced active material utilization, and worsened rate performance compared to the previous examples. Simultaneously, volume expansion becomes more prominent, and interfacial contact stability deteriorates. In Comparative Example 5, the lack of a BNNT spatial layer means that lithium dendrite growth is not suppressed by the BNNT network structure, increasing interfacial side reactions between the solid electrolyte and lithium metal, and significantly increasing the internal resistance after battery cycling.
[0157] (8) Example 1, Comparative Example 6
[0158] Comparative Example 6 illustrates the impact of different carbon materials loaded with sulfur on the cycle performance of lithium-sulfur solid-state batteries. Compared to the simple physical adsorption of sulfur on two-dimensional graphene sheets, the interpenetrating porous network of a three-dimensional graphene honeycomb structure can provide a sulfur loading rate of up to 90%. Its hierarchical channels can both encapsulate elemental sulfur and reserve mesoporous channels for the electrolyte. The three-dimensional honeycomb structure can withstand a 300% sulfur volume expansion without collapsing, while two-dimensional graphene sheets exhibit significant structural delamination after cycling. This synergistic effect of the "micro-nano cage" confinement effect and the conductive framework results in electrochemical performance far exceeding that of the two-dimensional graphene system.
[0159] (9) Example 1, Comparative Examples 7-10
[0160] Comparative Examples 7-10 illustrate the importance of the spatial layer composition materials proposed in this invention and their impact on the cycle performance of lithium-sulfur solid-state batteries. The absence of any component in the BNNT spatial layer affects the cycle performance of lithium-sulfur solid-state batteries: the lack of BNNT results in insufficient mechanical support and ion regulation channels, leading to dendrite penetration after lithium deposition and a higher risk of short circuits; the lack of lithium salt reduces the ionic conductivity of the interface layer, intensifying battery polarization and increasing polarization voltage; the lack of binder leads to insufficient mechanical strength of the BNNT layer, causing peeling during transfer and structural collapse during cycling; and the absence of hydrophilic additives reduces interfacial wettability, significantly increasing surface tension on the transfer film. The synergistic effect of different components in the BNNT spatial layer is crucial for maintaining a stable lithium deposition interface.
[0161] (10) Example 1, Comparative Examples 11-12
[0162] Comparative Examples 10-11 illustrate the impact of different space layer materials on the cycle performance of lithium-sulfur solid-state batteries. BNNTs exhibit excellent mechanical strength and thermal stability, effectively suppressing lithium dendrite penetration, while the brittleness of Al2O3 and the lower mechanical strength of LiF may lead to interfacial cracking. The interlayer nanochannels of BNNTs can promote uniform lithium-ion transport and partial desolvation, reducing overpotential, while the insulating properties of Al2O3 may hinder ion conduction, and LiF lacks similar nanostructure modulation capabilities. Therefore, BNNTs, as space layer materials, possess comprehensive advantages in suppressing dendrites, enhancing interfacial stability, and improving electrochemical performance.
[0163] Based on the disclosure and teachings of the foregoing specification, those skilled in the art can make appropriate changes and modifications to the above embodiments. Therefore, the present invention is not limited to the specific embodiments disclosed and described above, and some modifications and changes to the present invention should also fall within the protection scope of the claims of the present invention. Furthermore, although some specific terms are used in this specification, these terms are only for convenience of explanation and do not constitute any limitation on the present invention.
Claims
1. A lithium-sulfur solid-state battery, characterized in that, The lithium-sulfur solid-state battery comprises, in sequence: A three-dimensional confined sulfur cathode, wherein the three-dimensional confined sulfur cathode comprises polydopamine (PDA) coated three-dimensional graphene (3DG) loaded with sulfur; Solid electrolytes; and A lithium composite anode, comprising a lithium / lithium alloy anode and a space layer on the anode surface, wherein the space layer on the anode surface is a boron nitride nanotube (BNNT) composite film.
2. The lithium-sulfur solid-state battery according to claim 1, characterized in that, The three-dimensional confined sulfur cathode achieves dual confinement of sulfur through physical adsorption and chemical bonding by regulating the hierarchical pore structure of 3DG. The thickness of the PDA layer coating is 5-50 nm, and the coating rate is ≥90%. The 3DG is a three-dimensional honeycomb graphene; The 3DG has a hierarchical porosity, including macropores with a diameter of 50-500 nm, mesopores with a diameter of 2-50 nm, and micropores with a diameter of <2 nm, and a specific surface area of 500-5000 m². 2 / g; The active sulfur includes elemental sulfur, sulfurized polyacrylonitrile, or a combination thereof; The sulfur loading of the 3DG is 60-90%.
3. The lithium-sulfur solid-state battery according to claim 1, characterized in that, The BNNT composite film is formed by coating a transfer film with a mixture of BNNT and lithium salt. The BNNT has a diameter of 10-500 nm, a length of 1-100 μm, and an elastic modulus ≥0.5 TPa; The BNNT includes one or a combination of at least two of the following: single-walled boron nitride nanotubes, multi-walled boron nitride nanotubes, and nanoribbon boron nitride. The adhesion between the transfer film and the lithium composite negative electrode is 1-8 g / inch, and the thickness is 20-100 μm; The thickness of the space layer is 1-100 μm and the Young's modulus is ≥6 GPa.
4. The lithium-sulfur solid-state battery according to any one of claims 1-3, characterized in that, The BNNT mixed slurry contains BNNT, lithium salt, binder, and hydrophilic additive; The mass ratio of BNNT, lithium salt, binder, and hydrophilic additive is (1-20):(1-5):(1-5):(0.5-2). The lithium salts include one or more combinations of lithium fluoride, lithium nitride, lithium hexafluorophosphate, lithium trifluoromethanesulfonate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium perchlorate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium dioxalateborate, lithium difluorooxalateborate, lithium carbonate, lithium oxalate, lithium bicarbonate, lithium acetate, lithium halide, lithium sulfate, and lithium hydroxide. The adhesive comprises one or a combination of at least two of the following: polyvinyl alcohol, polyethylene oxide, polybutene-styrene, polystyrene-butadiene copolymer, polyvinylidene fluoride, polystyrene, polycarboxylic cellulose, cyanoacrylate, cyclodextrin, cyclic ether derivatives, polyurethane, methacrylate, epoxy resin, vinyl acetate polymer, polyimide, organofluoropolymer, organosiloxane, polyethylene glycol, polyethylene, polyvinyl chloride, polypropylene, glycerol, ethylparaben, and their derivatives; The hydrophilic additives include one or more combinations of carboxylates, sulfonates, sulfates, phosphates, imidazole ionic liquids, pyridine ionic liquids, quaternary ammonium ionic liquids, quaternary phosphorus ionic liquids, pyrrolidine ionic liquids, and piperidine ionic liquids. The transfer film material includes organic materials, which are selected from one or more of polyvinylidene fluoride, polyvinyl chloride, polyethylene, polypropylene, polystyrene, styrene-butadiene-vinyl nitrile copolymer, polyimide, polycarbonate, phenolic plastics, polyoxymethylene, polyethylene terephthalate, styrene-modified polymethacrylic acid, polysulfone, polytetrafluoroethylene, amino plastics, and epoxy resin, or their homopolymers or copolymers.
5. The lithium-sulfur solid-state battery according to any one of claims 1-4, characterized in that, The lithium / lithium alloy anode includes one or a combination of metallic lithium anode and lithium alloy anode. Preferably, the lithium alloy anode comprises an alloy of lithium with one or more of silicon, indium, silver, carbon, magnesium, aluminum, boron, tin, gallium, cobalt, gold, barium, bismuth, calcium, germanium, mercury, platinum, zinc, lead, antimony, cadmium, and cobalt. The thickness of the lithium / lithium alloy anode is 3μm-300μm, preferably 10μm-100μm; The thickness ratio of the space layer to the lithium / lithium alloy anode is (0.001-1):1, preferably (0.01-0.1):
1.
6. The lithium-sulfur solid-state battery according to any one of claims 1-5, characterized in that, The solid electrolyte comprises one or more of the following: sulfide solid electrolyte, oxide solid electrolyte, halide solid electrolyte, polymer solid electrolyte, or organic-inorganic composite solid electrolyte.
7. The lithium-sulfur solid-state battery according to any one of claims 1-6, characterized in that, Both the functionalized positive electrode and the lithium composite negative electrode include a current collector, which includes at least one of copper foil, aluminum foil, stainless steel foil, nickel foil, tin foil, carbon nanotube paper, carbon fiber paper, copper mesh, aluminum mesh, stainless steel mesh, nickel foam, and organic fiber film with metal plating on the surface.
8. A method for preparing a lithium-sulfur solid-state battery as described in any one of claims 1-7, comprising: (1) Preparation of PDA-coated 3DG-loaded sulfur mixture: 3DG is immersed in a buffer solution containing PDG and stirred for 6-12 hours to obtain PDA-coated 3DG composite material; sulfur powder and PDA-coated 3DG are mixed evenly and heated to the melting point of sulfur to melt the sulfur and penetrate into the graphene pores to obtain PDA-coated 3DG / S mixture. (2) Preparation of functionalized positive electrode: The above PDA-coated 3DG / S mixture is uniformly mixed with a binder, and a solvent is optionally added; the prepared mixed slurry is loaded onto the surface of the current collector and dried to obtain a functionalized positive electrode film; (3) Preparation of lithium composite negative electrode space layer: BNNT, lithium salt, binder and hydrophilic additive are uniformly mixed, and an optional solvent is added and stirred to obtain a mixed slurry. The mixed slurry is placed on the transfer film and dried to obtain the lithium composite negative electrode space layer. (4) Preparation of lithium composite anode: The space layer film is rolled onto the surface of the lithium / lithium alloy anode and the tabs are welded to obtain the lithium composite anode; (5) Assemble lithium-sulfur solid-state batteries: Assemble functionalized positive electrode, solid electrolyte, lithium composite negative electrode and encapsulation materials into lithium-sulfur solid-state batteries.
9. The method according to claim 8, characterized in that, The uniform mixing method described in step (1) is ball milling, wherein the ball milling speed is 100-600 rpm and the ball milling time is 3-6 h; The drying process described in steps (2) and (3) is at 80-100℃ and takes 8-12 hours. The adhesive mentioned in step (2) includes at least one of polyvinylidene fluoride (PVDF), polyacrylic acid (PAA), sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), sodium alginate (SA), polyethylene oxide (PEO), or polyimide (PI); The solvents mentioned in steps (2) and (3) include any one or a combination of at least two of N-methylpyrrolidone, tetrahydrofuran, dimethyl ethyl ether, dichloromethane, ethylene carbonate, dimethyl carbonate, diethyl carbonate, diethyl carbonate, methyl ethyl carbonate, ethylene glycol dimethyl ether, diethylene glycol monomethyl ether, tetraethylene glycol dimethyl ether, dimethyl sulfate, and polyetherketone; In step (2), the PDA coating 3DG / S: binder: solvent = (5-10): (2-3): (87-93).
10. The method according to claim 8, characterized in that, Step (3) The method of applying the paste to the transfer film includes any one or a combination of at least two of the following: coating, spraying, spin coating, rolling, and impregnation; In step (4), the pressure at which the space layer obtained in step (3) is rolled onto the lithium / lithium alloy negative electrode is 10-20 kN.
Citation Information
Patent Citations
Solid-state silicon-sulfur battery with gradually-changed electrolyte components and preparation method and application of solid-state silicon-sulfur battery
CN117154182A